2022
DOI: 10.1142/s1758825122500806
|View full text |Cite
|
Sign up to set email alerts
|

Static and Fatigue Tensile Behavior and Damage Mechanisms Analysis in Aged Flax Fiber/PLA Composite

Abstract: The aim of this paper is to analyze the effect of water aging of flax/PLA composites on their mechanical characteristics and damage mechanisms. The composites were manufactured with three-dimensional (3D) printer using bio-based material which is polylactic acid reinforced with flax fiber. The composites studied were subjected to water immersion at room temperature and tested in static and fatigue tensile tests for different immersion times. During mechanical tests, the acoustic emissions (AE) method was utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Yang [ 16 ], Peret [ 17 ], Almeida [ 18 ], Sui [ 19 ], and Kesentini [ 20 ] found that the moisture absorption characteristics of carbon fiber-reinforced polymer composites, under water immersion at temperatures of 25 °C, 70 °C, and 85 °C and hygrothermal environments of 80 °C, RH85%, and 80 °C, RH 90%, conformed to Fick’s law. Wu Rui [ 21 ] found that the later moisture absorption behavior of polymer composites deviated from Fick’s law.…”
Section: Introductionmentioning
confidence: 99%
“…Yang [ 16 ], Peret [ 17 ], Almeida [ 18 ], Sui [ 19 ], and Kesentini [ 20 ] found that the moisture absorption characteristics of carbon fiber-reinforced polymer composites, under water immersion at temperatures of 25 °C, 70 °C, and 85 °C and hygrothermal environments of 80 °C, RH85%, and 80 °C, RH 90%, conformed to Fick’s law. Wu Rui [ 21 ] found that the later moisture absorption behavior of polymer composites deviated from Fick’s law.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic emission is a common technology used to assess the damage evolution within polymer matrix composites [ 30 , 31 , 32 , 33 , 34 , 35 ]. In additive manufacturing, this technique has also been applied to 3D-printed polymer composites filled with continuous fibres [ 36 , 37 , 38 ] or short flax fibres [ 39 ] as well as 3D-printed sandwich structures [ 40 ]. However, as far as the author knows, no acoustic emission on 3D-printed CB/PLA has been reported in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Natural fibers have a hydrophilic behavior, which can have consequences on the fiber/matrix interfacial adhesion [21]. Several studies have shown that the water uptake in natural fiber-reinforced composites has an adverse effect on rigidity and strength [22][23][24][25][26] and some of them have focused Micro 2023, 3 on the influence of the water temperature on the absorption properties [27,28]. Malloum et al studied the influence of water immersion time on two cross-ply laminates ([0/90] s and [+45/−45] s ) of flax/Greenpoxy composite.…”
Section: Introductionmentioning
confidence: 99%